If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (z + 5)(z + -8) = 0 Reorder the terms: (5 + z)(z + -8) = 0 Reorder the terms: (5 + z)(-8 + z) = 0 Multiply (5 + z) * (-8 + z) (5(-8 + z) + z(-8 + z)) = 0 ((-8 * 5 + z * 5) + z(-8 + z)) = 0 ((-40 + 5z) + z(-8 + z)) = 0 (-40 + 5z + (-8 * z + z * z)) = 0 (-40 + 5z + (-8z + z2)) = 0 Combine like terms: 5z + -8z = -3z (-40 + -3z + z2) = 0 Solving -40 + -3z + z2 = 0 Solving for variable 'z'. Factor a trinomial. (-5 + -1z)(8 + -1z) = 0Subproblem 1
Set the factor '(-5 + -1z)' equal to zero and attempt to solve: Simplifying -5 + -1z = 0 Solving -5 + -1z = 0 Move all terms containing z to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -1z = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -1z = 0 + 5 -1z = 0 + 5 Combine like terms: 0 + 5 = 5 -1z = 5 Divide each side by '-1'. z = -5 Simplifying z = -5Subproblem 2
Set the factor '(8 + -1z)' equal to zero and attempt to solve: Simplifying 8 + -1z = 0 Solving 8 + -1z = 0 Move all terms containing z to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -1z = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -1z = 0 + -8 -1z = 0 + -8 Combine like terms: 0 + -8 = -8 -1z = -8 Divide each side by '-1'. z = 8 Simplifying z = 8Solution
z = {-5, 8}
| 0.5x^3-2x+2.5=0 | | -4=-(x-3)+6(x-2) | | 5(c-8-3)-3(2c+12)=-84 | | 2x+x+2=5x-10 | | .05x+.10(200-x)=.45x | | 0.09w=1.8 | | (a+4)(a+5)=0 | | -132=-39 | | -(c+10)+3(2c-6)= | | -132=39 | | -3v-v=16 | | -9b=-117 | | 35x+9=55 | | -n+2n=4 | | -8b=-117 | | -7x-3=4 | | 6n-7=2n+17 | | 11x-4x^2-344= | | 1/3(s-2)=s+4 | | (x+9)(x+9)=18 | | 344=11x-4x^2 | | 3(2z-1)=6z+5 | | -28=-7(1-8b)-5(4b-3) | | (x-2)(x+3)=24 | | 32x+1=3+6 | | 2x+1+6x=81 | | -6n+9=1-8n | | -17b=-2.21 | | -17=-2.21 | | 7x-3=2x-12 | | y=-4+3x | | -34e=-3.74 |